Nonlinear Impacts of Surface Exchange Coefficient Uncertainty on Tropical Cyclone Intensity and Air‐Sea Interactions - Robert G. Nystrom; Xingchao Chen; Fuqing Zhang; Christopher A. Davis (Geophysical Research Letters)
Abstract Tropical cyclone maximum intensity is believed to result from a balance between the surface friction, which removes energy, and a temperature/moisture (enthalpy) difference between the sea surface and the air above it, which adds energy. The competing processes near the air‐sea interface are controlled by both the near surface wind speed and the surface momentum (Cd) and enthalpy (Ck) exchange coefficients. Unfortunately, these coefficients are currently highly uncertain at high wind speeds. Tropical cyclone winds also apply a force on the ocean surface, which results in ocean surface cooling through vertical mixing. Using coupled atmosphere‐ocean and uncoupled (atmosphere only) ensemble simulations we explore the complex influence of uncertain surface exchange coefficients on storm‐induced ocean feedback and tropical cyclone intensity. We find that the magnitude of ocean cooling increases with storm intensity and Cd. Additionally, the simulated maximum wind speed uncertainty does not necessarily decrease when ocean feedback are considered.